PENGARUH PENGGUNAAN BAHAN AJAR BERMUATAN NILAI-NILAI KARAKTER DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR FISIKA KELAS XI SMAN 1 PADANG - Julita Kartini (PILLAR OF PHYSICS EDUCATION, 2014)
This research is aimed to examine the effect of the use of teaching materials loaded with character values ​​in cooperative learning model to learning outcomes TGT physics class XI SMA N 1 Padang.This is a type of quasi-experimental study with a design Randomized Control Group Only Design and population of all the students of class XI SMA N 1 Padang enrolled in school year 2013/2014 . Sampling was done by purposive sampling technique. The samples were class XI IPA 6 and class XI IPA 7. The research instrument is a written final test for cognitive learning outcomes, observation sheet for the affective domain of learning outcomes, and the scoring rubric for the psychomotor domain of learning outcomes. Analysis used two similarity test mean that the t test at the 0.05 significance level for the learning outcomes of cognitive, affective, and psychomotor.Based on the analysis of datathe results showed that there is a significant effect on the use of teaching materials loaded with character values ​​in cooperative learning model to learning outcomes TGT physics class XI SMA N 1 Padang